Estimating General Equilibrium Spillovers of Large-Scale Shocks - Kilian Huber (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Researchers use (quasi-)experimental methods to estimate how shocks affect directly treated firms and households. Such methods typically do not account for general equilibrium spillover effects. I outline a method that estimates spillovers operating among groups of firms and households. I argue that the presence of multiple types of spillovers, measurement error, and nonlinear effects can severely bias estimates. I show how instrumental variables, heterogeneity tests, and flexible functional forms can overcome different sources of bias. The analysis is particularly relevant to the estimation of spillovers following large-scale financial and business cycle shocks.
Keywords: 330; general equilibrium effects; spillovers; estimation; macroeconomic shocks; financial shocks